The construct validity of an abridged version of the general self-efficacy scale for adults with attention-deficit/hyperactivity disorder - Skliarova, Tatiana; Pedersen, Henrik; Hafstad, Hege; Vaag, Jonas Rennemo; Lara-Cabrera, Mariela Loreto; Havnen, Audun (Frontiers in Psychiatry, 2023)
Objectives The General Self-Efficacy (GSE) scale is a validated self-rated questionnaire increasingly used in mental health research. However, despite several psychometric advantages of the GSE scale, its validity in those diagnosed with attention-deficit/hyperactivity disorder (ADHD) has not yet been examined. Moreover, a shorter version of the GSE scale would contribute to a more rational use of resources in extensive multivariate studies. Therefore, as self-rated scales to measure self-efficacy in this population are lacking, the current study aims to develop a condensed version of the GSE for adults with ADHD. Methods A group of patient collaborators (user representatives) from an ADHD organization and health professionals shortened the original 10-item GSE scale to six items and evaluated the content validity of the revised scale. Second, 525 potential participants were invited to participate in a cross-sectional study conducted in 2021 (between January 19th and February 7th). Of them, 403 filled out the GSE-6 for ADHD and two scales measuring psychological well-being and mental health (the five-item World Health Organization Well-Being Index, WHO-5, and the four-item Patient Health Questionnaire, PHQ-4). The psychometric properties of the new scale were examined, testing a priori formulated hypotheses. Results The brief GSE-6 for ADHD displayed good internal consistency with a Cronbach’s α of 0.907. No floor or ceiling effect was detected. Exploratory and confirmatory factor analyses supported a one-factor structure. The GSE-6 also showed a moderate positive correlation with the WHO-5 (rs = 0.578) and a moderate negative correlation with the depression and anxiety rating scale PHQ-4 (rs = −0.595). Conclusion The 6-item GSE for ADHD was evaluated to have good content validity. The scale demonstrated good psychometric properties. The results indicate that the GSE-6 may help assess self-efficacy in adults with ADHD.